Effectiveness of a multimodal telemedicine educational intervention, implemented in times of the COVID-19 pandemic, for patients with heart failure and coronary artery disease (2021)
ABSTRACT: Aim: To evaluate the effectiveness of a multimodal telemedicine educational intervention for patients with heart failure (HF) or coronary artery disease (CAD), implemented in times of the COVID-19 pandemic, to maintain functioning, quality of life and achieve adherence to the recommendations. Methods: Before and after quasi-experimental study. Outcomes included adherence to medications, exercise and nutritional recommendations; Duke– DASI; quality of life with the Minnesota Living With Heart Failure Questionnaire (MLWHF) in HF and the SF-36 in CAD. Intervention: A multimodal telemedicine intervention (home cardiac rehabilitation), with educational videos on recommendations about exercise, nutrition and medication in the HF group and educational videos on exercise and delivery of the clinical practice guide for patients in the CAD group. Results: Comparative before and after analyzes were performed in 23 patients in the HF group and in 25 patients in the CAD group. The patients in both groups maintained adequate adherence to the pharmacological, nutritional and exercise recommendations. In the HF group, there was improvement in the MLWHF emotional domain, and in the CAD group, there was improvement in the SF-36 emotional role domain, with a decrease in the general health score. The rest of the domains were maintained in the evaluations. Conclusion: A multimodal educational intervention through telemedicine could be an alternative strategy to the face-to-face modality of cardiac rehabilitation, to maintain adherence to exercise, nutrition and medication and improve health related quality of life.